Prolonged exposure to freezing stress reduces the ability of chickpea seedlings to effectively tolerate extremely low temperatures - Nabati, Jafar; Nezami, Ahmad; Hasanfard, Alireza; Nemati, Zahra; Kahrom, Nastaran (Frontiers in Plant Science, 2023)
The duration and intensity of freezing stress are the most critical factors determining injury in autumn chickpeas, limiting their production and development. To evaluate the effects of freezing temperature and duration on the survival rate (SU%), as well as the physiological and biochemical characteristics of autumn chickpea seedlings, a study was conducted using five different temperatures (0, -6, -8, -10, and -12℃) and five different durations (1 h, 2 h, 3 h, 4 h, and 5 h) of exposure to freezing stress. The SU% of chickpea seedlings decreased to zero after exposure to temperatures of -10℃ and -12℃ for 5 hours. As the temperature decreased from -8℃ to -12℃ and the duration of exposure to freezing stress increased from 1 to 5 hours, the leaf membrane stability index decreased by 33%, 48%, 46%, 57%, and 58%, respectively. The highest and lowest total pigment contents were observed after 1 hour at 0°C and 5 hours at -12°C, respectively. The maximum photochemical efficiency of photosystem II (Fv'/Fm') was not affected by temperatures as low as -8°C in any of the time treatments during the recovery period. However, this parameter's value decreased as the freezing stress duration increased. At -12°C, the activity of ascorbate peroxidase, catalase, and peroxidase increased by 44.6%, 38.3%, and 33.0%, respectively, as the duration of stress was increased from 1 hour to 5 hours. A positive and significant correlation was observed between plant dry weight, membrane stability index, photosynthetic pigment content, and Fv'/Fm' with SU% after exposure to freezing stress. The minimum temperature and the maximum duration of freezing stress tolerance in chickpea seedlings were observed at -12°C for two hours. Our findings confirm that prolonging the freezing duration disrupts the defense mechanisms of chickpea seedlings. Therefore, future studies on breeding chickpeas tolerant to freezing stress should concentrate on attributes strongly correlated with SU%.